التغير في أدوار مؤسسات المجتمع في التنشئة الاجتماعية بالتركيز على (الأسرة - المدرسة - الأصدقاء) - بلاص، نجلاء عبدالرحمن وقيع الله (كلية دلتا العلوم والتكنولوجيا, 2021)
تهدف هذه الورقة إلى إبراز دور مؤسسات المجتمع (الأسرة -المدرسة -الأصدقاء) في عملية التنشئة الاجتماعية، إذ إن لهذه المؤسسات دور فاعل وبارز في تنشئة الطفل وتشكيل شخصيته. تهدف الورقة إلى محاولة توضيح دور مؤسسات المجتمع (الأسرة -المدرسة -الأصدقاء) في عملية التنشئة الاجتماعية، وفي بناء الأساس المتين والسليم لشخصية الطفل. تحديد ما يلزم القيام به لتفعيل دور هذه المؤسسات بما يحقق تنشئة اجتماعية سليمة للأطفال. معرفة أثر الأسرة والمدرسة والأصدقاء في عملية التنشئة الاجتماعية. وتنبع أهمية الورقة من كونها تسليط الضوء على دور ثلاث مؤسسات في المجتمع لها أهمية بالغه في عملية التنشئة الاجتماعية وذلك في ظل التحديات التي يفرضها التغيير. وهي: أولا: الأسرة: اكتسبت الأسرة ولا تزال تكتسب أهمية بالغة في حياة المجتمع الإنساني، وذلك لما تلعبه من دور بارز في حياة الفرد والمجتمع، ولأن الإنسان هو كائن متأثر ومؤثر في محيطة الاجتماعي الذي يكسبه القيم والمهارات والقدرات التي من خلالها بإمكانه لعب دوره المنوط به في واقعة الاجتماعي المعيش ثانيا: المدرسة: تطلع المدرسة بدور مهم في عملية التنشئة الاجتماعية ولاسيما أنها المؤسسة الاجتماعية الثانية بعد الأسرة تقوم بهذه العملية، وفيها يبدأ الطفل تكوين علاقاته وتفاعلاته مع المجتمع الخارجي. ثالثا: الأصدقاء: تلعب جماعة الرفاق أو الصدقاء دورا مهما في عملية التنشئة الاجتماعية خاصة أن الطفل يميل إلى تقليد ما يقوم به أقرانه من سلوك سليم أو سلوك غير سليم. اتبعت الورقة المنهج الوصفي التاريخي. توصلت الدراسة إلى عدد من النتائج أهمها: تقف الأسرة أمام تحديات كبيرة خاصة في ظل التغير والتطورات التي تحدث بسبب التكنولوجيا والتقنية والتي جعلت الآباء أمام امتحان صعب في كيفية تنشئة أبنائهم التنشئة الاجتماعية التي تحصنهم من الانزلاق في مغريات العولمة المختلفة. تحدد الأسرة قدر الإنسان في الحياة، لذا فإن فشل الأسرة في تقديم التنشئة الاجتماعية السليمة يلعب في غالب الأحيان دورا سلبيا في خلق شخصية غير سوية، وقد يسهم في تكوين السلوك المنحرف عند الطفل. كما خرجت الدراسة بعدة توصيات منها: على الآباء والمربيين أن يبادروا إلى توجيه الصغار بأهمية الصحبة الصالحة، وأن يرغبوهم في مرافقة ذوي الأخلاق الحسنة، وأن ينفروهم من رفقة ذوي النفوس الخبيثة والأخلاق الذميمة منذ الصغر، ولا يهملوا ذلك إلى مراحل تالية. وضع المناهج المدرسية التي تعتمد على المواهب والطموحات، والابتعاد عن مناهج الحشو المليئة بالمعلومات ذات الطابع الكمي والتي تنفر الطالب من المدرسة والمادة الدراسية، يجب تطوير المناهج ومواكبتها للتقدم التكنولوجي، حتى تقل نسبة الهروب والتسرب المدرسي. تفعيل وإعادة المناشط المدرسية (الجمعية الأدبية-جمعية الفلاحة والرياضة .... إلخ) لأنها تصقل مواهب الطلاب. This paper aims to highlight the role of community institutions (family - school - friends) in the process of socialization, as these institutions have an active and prominent role in the upbringing of the child and the formation of his personality. The paper aims to try to clarify the role of community institutions (family - school - friends) in the process of socialization, and in building a solid and sound basis for the child's personality. Determine what needs to be done to activate the role of these institutions in order to achieve a sound social upbringing for children. Know the impact of the family, school and friends in the process of socialization. The importance of the paper stems from the fact that it sheds light on the role of three institutions in society that are of great importance in the process of socialization, in light of the challenges imposed by change. They are: First: The family: The family has acquired and continues to gain great importance in the life of human society, because of the prominent role it plays in the life of the individual and society, and because the human being is an influenced and influential being in his social environment who acquires values, skills and abilities through which he can play his assigned role Tags in the social pension event. Second: The school: The school has an important role in the process of socialization, especially as it is the second social institution after the family to carry out this process, and in which the child begins to form relationships and interactions with the external community. Third: Friends: The group of comrades or friends plays an important role in the process of social upbringing, especially that the child tends to imitate the correct or improper behavior of their peers. The paper followed the historical descriptive approach The study found a number of results, the most important of which are: The family faces great challenges, especially in light of the change and developments that occur due to technology and technology, which have made parents face a difficult test in how to raise their children the social upbringing that protects them from slipping into the various temptations of globalization. Therefore, the family’s failure to provide a proper socialization often plays a negative role in creating an abnormal personality, and may contribute to the formation of deviant behavior in the child. The study also came out with several recommendations, including: Parents and educators should take the initiative to direct children to the importance of good companionship, and want them to accompany people with good morals, and alienate them from the companionship of those with malicious souls and bad morals from an early age, and they should not neglect this until later stages ... Which relies on talents and ambitions, and move away from filler curricula that are full of quantitative information that alienates the student from school and the subject. Curricula must be developed and kept abreast of technological progress, so that the school dropout rate decreases. Activating and re activating school activities (the Literary Association - The Peasant and Sports Association… etc) because it sharpens the talents of students.
Keywords: المؤسسات الاجتماعية -- التنشئة الاجتماعية -- القيم التربوية -- مرحلة الطفولة